Arrival and onset of breeding of three passerine birds in eastern Finland tracks climatic variation and phenology of insects. (28th April 2017) - Valtonen, Anu; Latja, Raimo; Leinonen, Reima; Pöysä, Hannu
Abstract : Anthropogenic climate change poses a challenge to the annual cycles of migratory birds. It has become urgent to understand whether migratory birds are able to advance their spring phenology when the climate is warming and whether they are able to adjust these phenological phases to the spring phenology in their breeding areas. In this work, we studied long‐term trends in first arrival and onset of breeding for three passerine birds in eastern Finland; the pied flycatcher Ficedula hypoleuca, the common redstart Phoenicurus phoenicurus and the great tit Parus major . The pied flycatcher and the common redstart are long‐distance migrants while the great tit is a partial migrant in Finland. We asked what environmental variables best explain the first arrival or onset of breeding, if there is evidence of 'thermal delay' (long‐term increase in the accumulated temperatures) at arrival or onset of breeding and if the interannual variation in the onset of breeding correlates with variation in spring phenology of local insects. We found that the pied flycatcher and the common redstart had advanced their first arrival (explained by increased temperatures at the migration route), but we found no long‐term change in the onset of breeding (explained by local temperatures). Also, the onset of breeding of the great tit is tracking local temperatures. We found no or only weak evidence of thermal delay at arrival or onset of breeding for any of the species. The onsets of breeding for the pied flycatcher and the great tit are also closely tracking the spring phenology of the local insects. The stable or increasing population sizes of all three species in Finland could be a result from their ability to effectively track climatic and environmental variation.